L’uomo europeo tra Husserl e Valéry: Profilo di un Amleto intellettuale - Valagussa, Francesco (Scenari, 2021)
The present essay focuses on the “foundation” of Europe, addressing the question of the European man, as it is posed at the end of the first World War (1914-1918) in some of the works by Valéry, Husserl and Musil. Europe can find its own asset on the economic field or play its geopolitical role only on the basis of a deep inquiry of its own culture, devoted, from its very beginning, to the clarification of concepts – the same peculiar culture which today finds itself in an overwhelming chaos. Therefore Valéry described the “European man” by giving the profile of an “intellectual Hamlet”, meditating on the life and death of truth.